EU Health Union: Legal Aspects and Digital Health - Cvahte Jasmina; Primec Andreja (Naše gospodarstvo/Our economy, 2024)
Recurrent health crises and outbreaks of infectious diseases of international concern have created a specific EU public health policy. Its role was further strengthened by the COVID-19 pandemic, which triggered the next stage in the integration process of the Member States: the European Health Union. The research is carried out using a literature review method (a review of literature and documents in the field of public health policy and the European Health Union) and a comparative-legal method for comparing EU legal acts on which the Health Union is based (endogenous comparison) and the legal acts of EU and the Republic of Slovenia (exogenous comparison). The findings are examined using a qualitative content analysis method, which allows for meaningful aggregation and use of the data under study to answer the research questions. The European Health Union builds on and extends existing areas of public health and requires greater integration between Member States. One of its most essential pillars is a single information system with a single database to improve the health of individuals, resilience to cross-border health crises, patient mobility, and joint research on the most severe diseases. Member States, including Slovenia, must follow EU public health commitments. As the Slovenian legislative proposal analysis on the digitalization of healthcare shows, this challenging task will also require respect for the institute (safeguards) of other areas of law.